Optimizing Image Focus for Shape From Focus Through Locally Weighted Non-Parametric Regression - Jang, Hoon-Seok; Muhammad, Mannan Saeed; Choi, Tae-Sun (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2019)
Shape from focus is a passive optical technique that uses multiple images with different focus levels. To compute the sharpness of each pixel in the image sequence, obtained by translating the object plane at a constant step size along the optical axis, focus measure operators are used. However, the focus measure operators do not provide the accurate focus value of the center pixel due to information loss between consecutive frames. In this paper, a local regression is proposed as a new fitting method for the focus curves. This method fits the focus curves, obtained by using one of the focus measure operators, by utilizing the weighted least squares regression as non-parametric regression. The experiments are performed on synthetic and real objects to demonstrate the effectiveness of the proposed method.
Keywords: RECOVERY